2018
DOI: 10.3390/resources7040079
|View full text |Cite
|
Sign up to set email alerts
|

Critical Natural Resources: Challenging the Current Discourse and Proposal for a Holistic Definition

Abstract: Studies on critical natural resources have grown in number over the last decade out of concern for resource availability and its potential impacts. Nonetheless, only a handful of studies explicitly define criticality for natural resources. Through a systematic literature review, we identified four main perspectives in the descriptions of critical natural resources: (1) economic importance is overemphasized at the expense of sociocultural and ecosystem support functions of natural resources; (2) a Western persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…One of the successful tactics for the development of SMEs is the utilisation of natural resources as a source of inspiration and creativity [19]. Natural resources are resources that are gained from nature and can be exploited for a variety of human requirements, such as industrial raw materials, food, medicine, and energy [20]. Natural resources can also be defined as resources that are found in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…One of the successful tactics for the development of SMEs is the utilisation of natural resources as a source of inspiration and creativity [19]. Natural resources are resources that are gained from nature and can be exploited for a variety of human requirements, such as industrial raw materials, food, medicine, and energy [20]. Natural resources can also be defined as resources that are found in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…An energy system powered by clean energy technologies differs fundamentally from one fueled by traditional hydrocarbon resources [62]. Moreover, the management of critical resources requires special guidance [75]. Thus, organizational, technological, and structural preparations are needed, along with special resources.…”
Section: Workforcementioning
confidence: 99%
“…As a highlight of the ambiguity involved with defining 'raw materials criticality' , Schellens and Gisladottir [9] gave a list of 23 distinct definitions across various review articles and gave a suggestion for a holistic definition. Alonso et al [1] identified 14 raw materials criticality features/metrics from 12 articles and sorted these into two categories: (a) institutional inefficiencies that cause resource unavailability and (b) physical constraints on amount and quality of resources.…”
Section: Identification and Selection Of Meaningful Features/metricsmentioning
confidence: 99%